ANALISIS DETERMINAN KINERJA KEUANGAN BANK SYARIAH: SEBUAH TINJAUAN LITERATUR - Atika Jauharia Hatta; Damayanti (Universitas Sarjanawiyata Tamansiswa, 2026)
Main Purpose - This study was conducted to examine and analyze the financial performance of Islamic banks. Design/methodology/approach - The method used in this study uses a qualitative literature review based on 30 Scopus-indexed scientific articles published between 2013 and 2023. Main Findings - This study found that financial performance is influenced by several factors, such as the characteristics of the board of directors (size of the board of directors, independence of the board of directors, frequency of board of directors meetings, gender diversity of the board of directors), characteristics of the sharia supervisory board (size of the sharia supervisory board, educational background of the sharia supervisory board, expertise of the sharia supervisory board), CEO power, quality of accounting disclosure, company size, share ownership, intellectual capital, environmental, CSR, corporate governance, zakat disclosure, charity disclosure, liquidity, capital adequacy, asset quality, management efficiency and audit committee. Theory and Practical Implications The theory that is widely used in research based on literature reviews is agency theory. Novelty - By reviewing articles indexed in Scopus, this study ensures that the sources used are from credible and quality journals, thus strengthening the validity and contribution of this study in providing comprehensive and up-to-date insights.